Nightwalker - Graham, Heather (Don Mills, Ont. : Mira Publications, 2009)
P.I. Dillon Wolf is fascinated by gambler Jessy Spearhawk and by the single word a dying man spoke: Indigo. From the glitz of the Vegas strip to a desert ghost town, the unlikely pair forge ahead with an investigation that will risk both their lives.
Keywords: Murder -- Investigation -- Fiction; Las Vegas (Nev.) -- Fiction; Romantic suspense fiction; Occult fiction